Performance of Different Cultivars of Mungbean in Coastal Region of Bangladesh - Islam, KN; Khan, MMH; Islam, MM; Uddin, MM; Latif, MA (SAARC Journal of Agriculture, 2020)
The study was conducted at farmers’ field of Itbaria, Patuakhali sadarupazila under Patuakhali district during January to April 2016under the agro ecological zone AEZ-13 (Ganges Tidal Flood plain). This site was located in between 22°14' and 22°29' North latitudes and in between 90°12' and 90°28' East longitudes of Bangladesh. Fifteenmungbean varieties viz., BARI Mung-1, BARI Mung-2, BARI Mung-3, BARI Mung-4, BARI Mung-5, BARI Mung-6, BINA Moog-4, BINA Moog-5, BINA Moog- 6, BINA Moog-7, BINA Moog-8, BU Mug-1, BU Mug-2, BU Mug-4 and Patuakhali local Mung were tested to select best suitable variety for costal region.The experiment was laid out in randomized complete block design (RCBD) with threereplications. Significant variation was observed among the different mungbeanvarities in respect of majority of the observed parameters.BU Mug-1 showed the tallest plant height while the tallest pod length was observed in BARI Mung-5. The highest number of branches per plant was found in BINA Moog-4 whereas the highest number of leaves per plant found for BARI Mung-6. The highest seed yield and yield attributes like number of pods per plant, number of seeds per pod and 1000 seed weight was recorded in BARI Mung-6 followed by BINA Moog-8 while Patuakhali local Mung produced the lowest yield and attributes. Most of the yield contributing factors of BARI Mung-6 wasfavorable for better yield in coastal region of Bangladesh. Hence the mungbean production can be increased by introducingBARI Mung-6 in costal region. SAARC J. Agri., 18(1): 161-172 (2020)